AN EXPLORATORY STUDY OF JAMU AND TRADITIONAL SKILL THERAPIES AT THE GRIYA SEHAT RUMAH CANTIK ARTIK - AS, Indarto; Kirwanto, Ag; Khairun Nisa, Zakiyya (Jurnal Jamu Kusuma, 2025)
Griya Sehat Rumah Cantik Artik, a traditional health care facility in Klaten Regency, offers jamu and traditional skill therapies to enhance physical fitness and address health concerns. This study aimed to explore the application of jamu therapy and traditional skill therapies at Griya Sehat Rumah Cantik Artik. The present study employs a qualitative research approach, characterized by an exploratory study design. In-depth interviews, observations, and documentation studies are utilised as data collection instruments, with a total of four informants participating in the study.  The results of the study showed various types of jamu for fitness improvement. These included dried herbs and tea such as wedang uwuh, butterfly pea, saffron, and roselle; jamu in the form of powder, including moringa powder and zuriat powder; capsule, including moringa capsules, channa B pollen, and buminoxhan; instant jamu, including instant ginger-lemongrass, instant turmeric-tamarind, and others.  In addition, tea formulations were composed of ingredients following B2P2TOOT recipes for hypertension, cholesterol, uric acid, obesity, and ulceration. This kind of tea, including mint tea, wedang uwuh, gempur lemak, and for diabetes. The available traditional skill therapy range encompasses cupping, acupuncture, acupressure, totok wajah, body massage, boreh, scrub, spice bath, ratus Miss V, and ear candle. Consequently, it can be deduced that enhancing physical fitness and well-being can be achieved by implementing jamu and traditional skill therapy.